Addressing Mood Disorder Diagnosis' Stigma With an Honest, Open, Proud (HOP)-Based Intervention: A Randomized Controlled Trial - Modelli, Arlete; Candal Setti, Viviane P.; van de Bilt, Martinus Theodorus; Gattaz, Wagner Farid; Loch, Alexandre Andrade; Rössler, Wulf (Frontiers in Psychiatry, 2021)
Introduction: The public stigma and self-stigma contribute to the dilemma of disclosing or not one's own mental illness diagnosis. Studies suggest that revealing it diminishes stress, besides helping with self-esteem. Honest, Open, Proud (HOP) is a group program that aids in the process of deciding on it, reducing its impact. Considering the relevance of this issue, the present study aimed to apply a HOP-based intervention in a group of patients diagnosed with mood disorders. Methods: A randomized controlled clinical trial was used, including 61 patients with mood disorders, of whom 31 were diagnosed with depression and 30 were diagnosed with bipolar disorder. They were randomly placed on the intervention (HOP) or the control group (unstructured psychoeducation). The evaluations occurred before (T0) and after (T1) the sessions. We administered eight scales, from which three presented relevant results: Coming Out with Mental Illness Scale (COMIS), Cognitive Appraisal of Stigma as a Stressor (CogApp), and Authenticity Scale. Results: The intervention groups (depression and bipolar) did not present a significant change regarding the decision to disclose their diagnostics. However, the depression group showed a decrease on the perception of stigma as a stressor (T0 = 0.50 vs. T1 = −1.45; p = 0.058). Improvements in post-intervention results were seen for both groups (depression and bipolar) on the Authenticity Scale—self-alienation subscale (T0 = 10.40 vs. T1 = 12.37, p = 0.058). Conclusion: Our HOP-based intervention appeared to be an important program to aid patients in facing stigma stress, showing positive effects, whether helping to diminish stress or to improve self-conscience, both of which have indirect effects on self-stigma. As it is a compact program, it can bring benefits when applying to public health institutions.